2011
DOI: 10.1515/jpm.2011.012
|View full text |Cite
|
Sign up to set email alerts
|

miRNA expression profiling in formalin-fixed and paraffin-embedded placental tissue samples from pregnancies with severe preeclampsia

Abstract: Two of the up-regulated miRNAs (miRNA-182* and miRNA-133b) are putative regulators of the transcript variants 1 and 2 of the BCL2-like gene, which controls apoptosis. miRNA-182* is also a probable angiogenesis regulator via angiogenin and VEGF-B. Apoptosis and angiogenesis are major mechanisms presumed to be involved in the pathogenesis of preeclampsia. Moreover, usability of qPCR technique based miRNA profiling for FFPE tissues was proofed. Hence FFPE tissue is the most widely used material for retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…Several reports (Pineles et al 2007, Roman et al 2008, Zhu et al 2009, Enquobahrie et al 2011, Mayor-Lynn et al 2011, Noack et al 2011 have illustrated the differential expression of placental miRNAs in PE patients. However, except for miR-210 (elevated in preeclamptic placenta) (Pineles et al 2007, Zhu et al 2009, Enquobahrie et al 2011, miR-181a (elevated in preeclamptic placenta) , Zhu et al 2009), and miR-1 (decreased in preeclamptic placenta) (Roman et al 2008, Zhu et al 2009, Enquobahrie et al 2011, there was little overlap among these data; this could have resulted from differences in the sample collections (including the gestational ages of the placentas and the processing of the placentas), profiling methods and patients' ethnicities ).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports (Pineles et al 2007, Roman et al 2008, Zhu et al 2009, Enquobahrie et al 2011, Mayor-Lynn et al 2011, Noack et al 2011 have illustrated the differential expression of placental miRNAs in PE patients. However, except for miR-210 (elevated in preeclamptic placenta) (Pineles et al 2007, Zhu et al 2009, Enquobahrie et al 2011, miR-181a (elevated in preeclamptic placenta) , Zhu et al 2009), and miR-1 (decreased in preeclamptic placenta) (Roman et al 2008, Zhu et al 2009, Enquobahrie et al 2011, there was little overlap among these data; this could have resulted from differences in the sample collections (including the gestational ages of the placentas and the processing of the placentas), profiling methods and patients' ethnicities ).…”
Section: Discussionmentioning
confidence: 99%
“…Enquobahrie et al (2011) further confirmed the downregulation of previously identified miRNA candidates (miR-1, miR-328, miR-139-5p, miR-500, and miR-1247) and found two novel miRNA candidates to be downregulated in pregnancies complicated by PE (miR-584 and miR-34c-5p). Noack et al (2011) identified another six miRNAs to be overexpressed in five cases with severe PE who delivered at gestational age ranging from 29 to 37 weeks (let-7b, miR-302*, miR-104, miR-128a, miR-182*, and miR-133b).…”
Section: Differential Expression Of Mirnas Between Pre-eclamptic and mentioning
confidence: 99%
“…Although different hypotheses have been put forth, the underlying etiology of preeclampsia is unknown (32). Analysis of miRNAs from formalin-fixed placental specimens of preeclampsia patients has demonstrated altered miRNA profiles (33)(34)(35). Deep sequencing of miRNAs obtained from placental tissues suggests that, in the setting of preeclampsia, the isomiR profile is altered with increased 3′ end addition of an adenosine (36).…”
mentioning
confidence: 99%